A new scandium and niobium co-doped cobalt-free perovskite cathode for intermediate-temperature solid oxide fuel cells. (15th January 2016) - Chen, Guihua; Wang, Yong; Sunarso, Jaka; Liang, Fengli; Wang, Huanping
Abstract: In exploring new cobalt-free perovskite oxide cathodes for intermediate temperature SOFCs (solid oxide fuel cells), Sc and Nb co-doped SrFeO3 -based perovskite, SSNF (SrSc0.175 Nb0.025 Fe0.8 O3−δ ) was synthesized. Powder X-ray diffraction, high resolution transmission electron microscopy and SAED (selected area electron diffraction) showed that SSNF crystallized in the tetragonal space group P4/mmm (#123) with lattice parameters of a = 3.912 Å and c = 7.794 Å. Upon heating from 400 °C to 1000 °C, the oxygen non-stoichiometry (δ) of SSNF increased from 0.19 to 0.47, concurrent with a decrease in the average valence state of iron from 3.73 to 3.03. The electrical conductivity of SSNF followed semi-conducting thermal dependence behavior, with values of 3.7–9.4 S cm −1 at 350–750 °C. O2 -TPD (oxygen temperature programmed desorption) indicated the onset of Fe 4+ reduction at ∼500 °C. SSNF exhibited a low thermal expansion coefficient value of 16.2 × 10 −6 K −1 (70–900 °C), as anticipated by excluding cobalt from the perovskite lattice. SSNF was relatively inert to the SDC (Sm0.2 Ce0.8 O1.9 ) electrolyte up to 1000 °C. These features, and its low ASR (area specific resistance) of 0.236 Ω cm 2 at 600 °C, denote the potential of SSNF and the opportunity to create new structures with improved performance through a co-doping strategy. Highlights: Development of a new cobalt-free composition for cathodes of solid oxide fuel cells. Complementary use of powder XRD and HRTEM to determine the structure of SSNF. Correlation of oxygen non-stoichiometry to the conductivity, TECs and ORR performance. SSNF shows high ORR activity between 550 and 750 °C with low TEC.